2018
DOI: 10.1111/jep.13035
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy: How to work with evidence in daily practice

Abstract: Rationale, aims, and objectives: The concept of evidence-based health care has gained increasing currency over the past decades; however, questions persist regarding how to overcome the gap between research and health care practice. The question arises whether this gap derives from a true knowledge deficit or from physiotherapists' perception of working with evidence. The aim of the current study was to illuminate changes to the meaning of working with evidence experienced by a cohort of physiotherapists follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The informants stated that a barrier towards putting research-based knowledge into practice was that they needed more resources. Our findings support the proposal of Snöljung and Gustafsson [40], who note that the barriers encountered by PTs in their implementation of EBP may be related to a lack of expertise and a limited understanding of scientific research. Further, in accordance with our findings, previous studies have also shown that most PTs are interested in improving their EBP skills and that they have a positive attitude towards EBP [41,42].…”
Section: Discussionsupporting
confidence: 88%
“…The informants stated that a barrier towards putting research-based knowledge into practice was that they needed more resources. Our findings support the proposal of Snöljung and Gustafsson [40], who note that the barriers encountered by PTs in their implementation of EBP may be related to a lack of expertise and a limited understanding of scientific research. Further, in accordance with our findings, previous studies have also shown that most PTs are interested in improving their EBP skills and that they have a positive attitude towards EBP [41,42].…”
Section: Discussionsupporting
confidence: 88%
“…1 . Applying EBP in primary health care settings ensures that clinicians use effective interventions to achieve desired outcomes, thereby contributing to the best quality of care [ 4 ]. However, there are several barriers for EBP and the components separately (evidence-based knowledge, clinical expertise, and patient values within a given context) that must be overcome in order to succeed with increased quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…The perspective of older people is fundamental in EBP [ 25 , 28 , 29 ], as they have their own individual and meaningful rationale for participating in interventions [ 30 ]. Considering the views of older people is important for identifying their needs, which in turn helps providers to develop appropriate and responsive services [ 31 ].…”
Section: Introductionmentioning
confidence: 99%